Atomic Dispersion of Pt Clusters Encapsulated Within ZSM‐5 Depending on Aluminum Sites and Calcination Temperature. Issue 2 (12th October 2022) - Zhang, Shaocheng; Li, Yufeng; Ding, Chuanmin; Niu, Yanxia; Zhang, Yafeng; Yang, Bing; Li, Gangsen; Wang, Junwen; Ma, Zili; Yu, Li-Juan
Abstract : Atomically dispersed Pt atoms encapsulated inside ZSM‐5 zeolites are synthesized via thermally induced dispersion under oxygen atmosphere. Dispersion of Pt clusters within ZSM‐5 and silicate‐1 is compared to investigate its dependence on the support and calcination temperature. Detailed density functional theory (DFT) calculations are applied to rationalize the dispersion process, which includes the detachment of Pt species from the bulk and the migration of volatile PtO x species, both of which are accelerated by thermal treatment at high temperature. DFT results also indicate that Al atoms within zeolites provide the anchoring sites to retain the dominated PtO species, though their interaction with the support is weakened with the increase in temperature. Our findings suggest that successful dispersion depends on the strong metal–support interaction and thermal treatment at moderate temperature (500 °C) which is crucial to balance the detachment and fixation of Pt atoms. This study paves the way to further understand the dispersion mechanism and assist in the development of stable single‐atom catalysts. Abstract : Well‐dispersed Pt single atoms encapsulated inside ZSM‐5 are achieved. Density functional theory results reveal that Al sites play a crucial role to anchor Pt atoms which improves the dispersity of Pt clusters and stability of PtOx species. The successful dispersion depends on strong metal–support interaction and thermal treatment at moderate temperature.